2015
DOI: 10.3171/2014.11.jns141741
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia without neurovascular compression presents earlier than trigeminal neuralgia with neurovascular compression

Abstract: I n 1934, Dandy proposed neurovascular compression (NVC) as an etiology for trigeminal neuralgia (TN).In his series, he reported that the superior cerebellar artery caused NVC in 30.7% of patients. 6 He noted veins, tumors, and vascular and cranial malformations as other "gross findings" causing compression of the trigeminal nerve; nevertheless, in 40% of cases, he observed no evidence of a gross lesion.6 He did document, however, that his posterior fossa approach did not allow for visualization of the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 41 publications
(53 reference statements)
2
46
0
2
Order By: Relevance
“…that TN without NVC is more prevalent in younger individuals (6). These findings suggest contributions of genetic and epigenetic factors to the pathophysiology of classical TN, especially in patients without severe NVC.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…that TN without NVC is more prevalent in younger individuals (6). These findings suggest contributions of genetic and epigenetic factors to the pathophysiology of classical TN, especially in patients without severe NVC.…”
mentioning
confidence: 65%
“…Ultrastructural studies on biopsied trigeminal roots showed axonal a Gain-of-Function Mutation in nav1. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigeminal neuralgia (TN) is characterized by paroxysmal facial neuropathic pain along one or more branches of the trigeminal nerve, often triggered by innocuous stimuli, such as light touch, eating, shaving, or applying makeup [30]. Although neurovascular compression of the trigeminal nerve is prevalent in patients with TN, symptoms can occur in the absence of nerve compression or only in a subpopulation of patients with nerve compression [5; 68; 69; 77], which suggests the contribution of other factors in disease manifestation. The sodium channel blockers carbamazepine (CBZ) and oxcarbazepine are the first-line treatment for classical TN [30], which supports involvement of sodium channels in the pathophysiology of TN.…”
Section: Nav16 In Trigeminal Neuralgiamentioning
confidence: 99%
“…[17, 18] Since TN is considered a clinical description disease, magnetic resonance imaging (MRI) is not the standard of care in diagnosis and treatment and, consequently, proof of compression is not required nor often confirmed for treatment or surgery in the majority of cases. A review of autopsy studies shows NVC in 90%–100% of TN patients, yet also in 16%–58% of patients without TN.…”
Section: Introduction and Etiologymentioning
confidence: 99%